Internalisasi Nilai Budaya Adat Wewengkon Citorek dalam Pembelajaran Sejarah - Weny Widyawati Bastaman; Rahayu Permana (Tsaqofah, 2018)
Historical learning is not just a factual information or introduction of concepts to be used as student knowledge. Historical learning seeks to develop students' critical and logical thinking skills about the various social phenomena so proficient in life in society. Learning of history based on local culture is expected to generate local potential that during this marginalized and teralinasi from public attention. The description of education that can be explained by researchers in the Lebak region, especially in the location of the research study has not touched and introduces its local culture specifically, either in special historical learning or in mulok learning. The goal to be achieved is to provide knowledge to learners to know about the local culture in the region. This is because the school is an institution that was formed to provide educational process that is not possible given in the family or community, thus through the history of learning in school is expected to learners in addition to knowing also through cultural history-based learning historically also aims to prepare learners so they have values localization inherited from their predecessors in the area. Approach of history material based on local culture is considered important to be taught in order to motivate learners in SMAN 1 Rangkasbitung.